STRATEGY TO ENHANCE SOCIAL ENTREPRENEURSHIP THROUGH THE USE OF NEW MEDIA WITHIN MALAYSIA GLOBAL INNOVATION AND CREATIVE CENTRE (MaGIC) - Munirah Mohd Jidi; Nur Faithzah Jamian; Erratul Shela Eshak; Norlida Zakirai@Zakaria (International Journal of Accounting, Finance and Business, 2021)
This study is being conducted to determine a strategy for enhancing social entrepreneurship within Magic by digital media. The aim of this study was to determine the relationship between the use of social media and the growth of social entrepreneurship through qualitative analysis. The information for this study was gathered from entrepreneurs who were selected to meet the criteria. Two entrepreneurs have been chosen to collect data for the research. Data is collected through an interviewing process that is focused on questions that have been created in accordance with the study purpose and research query. The findings shows that both informants stated that social media is very significant in developing social entrepreneurship. The findings also show that social entrepreneurship and improving living standards are related. This research's contribution is that it provides entrepreneurs with a brilliant idea for expanding their business using social media and considers solutions to problems relevant to social entrepreneurship.